1999
DOI: 10.1007/bf02753843
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland protection by amifostine in high-dose radioiodine therapy of differentiated thyroid cancer

Abstract: Parenchymal damage in salivary glands induced by high-dose radioiodine treatment can be reduced significantly by amifostine. This may help to increase patients' quality of life in differentiated thyroid cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…Intravenous amifostine, an organic thiophosphate, is a recent addition to the drug armamentarium to combat the effects of irradiation [54][55][56][57]. Within the tissues, amifostine undergoes dephosphorylation to its active metabolite WR-1065.…”
Section: Strategies For Prevention and Treatmentmentioning
confidence: 99%
“…Intravenous amifostine, an organic thiophosphate, is a recent addition to the drug armamentarium to combat the effects of irradiation [54][55][56][57]. Within the tissues, amifostine undergoes dephosphorylation to its active metabolite WR-1065.…”
Section: Strategies For Prevention and Treatmentmentioning
confidence: 99%
“…Hier ist die Angabe der Spannweite angezeigt. Bei sechs Publikationen (4%; 1%-10%) wird die Standardabweichung angegeben, obwohl das 95%-Konfidenzintervall oder wenigstens der Standardfehler sinnvoller gewesen wären [24,38,54,78,135,154].…”
Section: Qualitätsanalyse Der Zeitschrift "Strahlentherapie Und Onkolunclassified
“…Several clinical phase-II studies have demonstrated some clinical efficacy of amifostine [1,3,4,9,[11][12][13]. A recent randomized study has investigated the effect of amifostine in patients undergoing definitive or postoperative radiotherapy for head-and-neck cancers [10].…”
mentioning
confidence: 99%